Optical and Structural Properties of PEO-Like Plasma Polymers - Mota, Rogério Pinto [UNESP]; Bigansolli, Antonio Renato [UNESP]; Antunes, Érica Freire [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Da Cruz, Nilson Cristino [UNESP]; Honda, Roberto Yzumi [UNESP]; Algatti, Mauricio Antonio [UNESP]; Aramaki, Emilia Akemi [UNESP]; Kayama, Milton Eiji [UNESP] (Taylor & Francis, 2002)
This paper deals with the study of optical, structural and biocompatible properties of PEO-like plasma polymerized films resulting from RF excited diethylene glycol dimethyl ether (CH 3 O(CH 2 CH 2 O) 2 CH 3 diglyme) glow discharges. The study was carried out using visible-ultraviolet and FTIR spectroscopies and contact angle measurements. FTIR spectra of plasma polymerized diglyme showed a stronger presence of ethylene glycol groups in film structure for lower RF power levels. The contact angle measurements for water revealed an increasing from 30° to 62,5° when the RF power was varied from 2 to 45 W, indicating the decreasing of the hydrophilic character of diglyme films with the increasing of RF power. This trend is in agreement with FTIR results. The data from visible-ultraviolet reflectance and transmittance spectra revealed alterations on optical properties of plasma polymerized diglyme films. The film's optical gap varied from 3.8 to 3 eV for RF power running from 5 to 45 W.